The People's Republic of China connecting Europe? - Julia Gruebler (Asian Development Bank Institute (ADBI), 2020)
The significance of the Belt and Road Initiative (BRI) of the People's Republic of China (PRC) for Europe is increasing. The diplomatic initiative "16+1," comprising 11 Central and East European EU member states and five Western Balkan economies, expanded to a "17+1" format in April 2019, when Greece officially joined the cooperation forum. In relative terms, the Western Balkans are expected to benefit the most from the BRI, as they show particularly high deficiencies in infrastructure and to date have limited access to EU grants. The economic effects of infrastructure projects in CESEE would, however, trickle through European production and supply chains, with an impact on economies not directly subject to construction plans. EU initiatives presented in 2018 may help to increase complementarity between Chinese and European infrastructure development plans, as well as reducing risks for some European economies, such as unsustainable debt or the rise of new barriers resulting from increased competition for Chinese investments. The BRI is about to change physical and digital connectivity within Europe, while the EU has yet to become an active player engaging in the initiative, in order to enable improved connectivity in Europe to drive economic convergence and not political divergence. The need to establish a level playing field for trade, investment, and its financing has become even more urgent, with the United States undermining multilateralism and adopting a noncooperative stance towards the EU and an openly hostile position towards the PRC.
Keywords: E22; H54; F14; F21; L91; O18; 330; Belt and Road; infrastructure; connectivity; EU; People's Republic of China (PRC); Western Balkans